2021
DOI: 10.5935/1676-2444.20210002
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord constriction as a cause of intrauterine fetal death

Abstract: The history of muscle biopsy dates back to 1860, when Duchenne first performed a biopsy on a patient with symptoms of myopathy (1) . Since then, the basic and clinical science of muscle and muscle disease has gone through three stages of development: the classical period, the modern stage and the molecular era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Which is correlating with our study although the incidence of long cords in our study is minimal and presence of hyper coiling is also evident in short cord's as well. Kuiava, et al 13 found that umbilical cord constriction / stenosis lead to intrauterine growth retardation with increased perinatal mortality. He also found the highest rate of cord stenosis were diagnosed in second trimester and mostly in male babies which is aptly coinciding with this study.…”
Section: Discussionmentioning
confidence: 99%
“…Which is correlating with our study although the incidence of long cords in our study is minimal and presence of hyper coiling is also evident in short cord's as well. Kuiava, et al 13 found that umbilical cord constriction / stenosis lead to intrauterine growth retardation with increased perinatal mortality. He also found the highest rate of cord stenosis were diagnosed in second trimester and mostly in male babies which is aptly coinciding with this study.…”
Section: Discussionmentioning
confidence: 99%